2018
DOI: 10.1177/1558944718795281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screw Length and Geometry on Interfragmentary Compression in a Simulated Proximal Pole Scaphoid Fracture Model

Abstract: The design of headless compression screws allows for maximal interfragmentary compression at the screw midpoint; we questioned whether a short screw centered on the fracture site resulted in superior compression to a longer, noncentered screw. Our data suggest that centering a small screw (10 mm) along a proximal fracture generates significantly less interfragmentary compression than a longer, noncentered screw. Our results demonstrate that balance between maximizing screw length and centering the screw on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Furthermore, Patel et al showed no difference in compression between screws despite expecting greater compression with larger screw pitch. 25 Although the threaded nail has a larger screw pitch compared with the partially threaded or fully threaded screws, our study demonstrated that it provided the least amount of compression.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, Patel et al showed no difference in compression between screws despite expecting greater compression with larger screw pitch. 25 Although the threaded nail has a larger screw pitch compared with the partially threaded or fully threaded screws, our study demonstrated that it provided the least amount of compression.…”
Section: Discussionmentioning
confidence: 59%
“…When fixing scaphoid fractures with a screw, surgeons usually aim for a centre pathway with the tip reaching as far as the opposite pole. Some authors claim that perpendicular placement to the fracture is most important, while others emphasise screw length [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A biomechanical study by Patel et al [40] indicated that in a proximal fracture, a longer non-perpendicular screw provided more compression than a shorter perpendicular screw. In our study, vBMD values were higher at the two poles and the subchondral region to the capitate than in the centre of the scaphoid.…”
Section: Discussionmentioning
confidence: 99%
“…Maximizing screw length provides greater resistance to bending and rotational forces and greater bony purchase for stability. 10 Here we describe a technique of percutaneous dual antegrade screw fixation for proximal phalanx fractures with minimal violation of the extensor mechanism which facilitates immediate postoperative range of motion without splinting, utilizing only a soft dressing and buddy strapping.…”
mentioning
confidence: 99%
“…Screw convergence provides resistance to shortening and screws of similar length more widely distribute implant loads. Maximizing screw length provides greater resistance to bending and rotational forces and greater bony purchase for stability 10…”
mentioning
confidence: 99%